Effects of multi-resistant ScALDH21 transgenic cotton on soil microbial communities - Yang, Qilin; Wang, Jiancheng; Zhang, Dawei; Feng, Hui; Bozorov, Tohir A.; Yang, Honglan; Zhang, Daoyuan (Frontiers in Microbiomes, 2023)
Environmental safety assessment of transgenic cotton 2 Transgenic crops are increasingly prevalent worldwide, and evaluating their impact on soil microbial communities is a critical aspect of upholding environmental safety. Our previous research works demonstrated that overexpression of ScALDH21 from desiccant-tolerant moss, Syntrichia caninervis, in cotton revealed multi-resistance to drought, salt, and biotic stresses. We conducted metabarcoding using a high-throughput sequencing to evaluate the effect of ScALDH21 transgenic cotton on soil microbial communities. We further conducted soil tests to analyze the chemical properties of transgenic and non-transgenic cotton, including the total content and availability of chemical elements (K, P, and Na), organic matter, and pH value. Both transgenic and non-transgenic cotton fields exhibited soil pH values higher than 8. The presence of transgenic cotton significantly enhanced the availability of available K and the total content of total P in the soil. in aAlpha and beta diversity indices of soil microbiota showed no difference between two transgenic and non-transgenic cotton groups. Dominant clades of fungal and bacterial genera were equivalent at the phylum and genus levels in all three groups.The correlation analysis of microbial communities and soil environmental factors revealed the absence of significant differences between transgenic and non-transgenic cotton genotypes. Functional predictions of soil microbial communities indicated that microbial community function did not show significant differences between transgenic and non-transgenic cotton samples. These findings are essential for evaluating the environmental effects of transgenic crops and supporting the secure implementation of transgenic cotton.